Land suitability analysis for settlement development based on geographic information system in Temanggung Regency - Dhafa Yoga Nurpratama (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Temanggung Regency has experienced a population growth of 11.12% over the last decade, which implies an increasing demand for settlement land in the future. On the other hand, Temanggung Regency has complex topographic conditions with variations ranging from flat to very steep terrain, necessitating land suitability assessment to support sustainable settlement development. This study aims to provide recommendations for settlement development by generating land suitability analysis for settlement areas. This research employs a quantitative approach utilizing spatial data as the primary analytical material. The methods used include scoring analysis and overlay techniques through geographic information system software. The results of this study classify settlement land suitability into four categories, non-developable, low/difficult development, reserved development, and recommended development. The recommended development land covers an area of 14,216 hectares or 16.41% of Temanggung Regency's total area, with the highest distribution found in Temanggung District, Pringsurat District, Kedu District, Kranggan District, and Parakan District. This research is expected to serve as a recommendation for the Temanggung Regency government in planning settlement development within the region. The findings indicate that settlement expansion opportunities are spatially concentrated in relatively flat, accessible, and low-hazard areas, providing practical guidance for spatial planning and land use control.